2022
DOI: 10.1038/s41467-022-28943-z
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate complexation enhances hydrothermal transport of rare earth elements in alkaline fluids

Abstract: Rare earth elements (REE), essential metals for the transition to a zero-emission economy, are mostly extracted from REE-fluorcarbonate minerals in deposits associated with carbonatitic and/or peralkaline magmatism. While the role of high-temperature fluids (100 < T < 500 °C) in the development of economic concentrations of REE is well-established, the mechanisms of element transport, ore precipitation, and light (L)REE/heavy (H)REE fractionation remain a matter of debate. Here, we provide direct evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 86 publications
(165 reference statements)
0
10
0
Order By: Relevance
“…In addition, Kozlov et al (2018), in their study of Ti–Nb mineralisation in the late stage Petyayan-Vara REE carbonatites of the Vuoriyarvi Massif in Russia, reported that Nb and Ti migrated together in metasomatic fluids, in which the ligands were F, and to a lesser extent, PO 4 3– and CO 3 2– . The significance of an alkaline component of fluids has previously been described in relation to REE transportation and fractionation (Anenburg et al , 2020; Louvel et al , 2022). Together with higher levels of F at Kangankunde compared to Chilwa Island, this may have facilitated Nb-enrichment of Kangankunde medium-grade fenite.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, Kozlov et al (2018), in their study of Ti–Nb mineralisation in the late stage Petyayan-Vara REE carbonatites of the Vuoriyarvi Massif in Russia, reported that Nb and Ti migrated together in metasomatic fluids, in which the ligands were F, and to a lesser extent, PO 4 3– and CO 3 2– . The significance of an alkaline component of fluids has previously been described in relation to REE transportation and fractionation (Anenburg et al , 2020; Louvel et al , 2022). Together with higher levels of F at Kangankunde compared to Chilwa Island, this may have facilitated Nb-enrichment of Kangankunde medium-grade fenite.…”
Section: Discussionmentioning
confidence: 95%
“…The experiments also noted LREE–HREE decoupling in the presence of alkalis, particularly K, with increased solubility of HREE, which would accord with the low LREE/HREE whole-rock ratios of the potassic breccia at Chilwa Island and help account for (La/Yb) cn ratios of fenite REE minerals being lower than those in carbonatite. The key role that alkaline fluids may play in the mineralisation of hydrothermal REE fluorcarbonates by promoting the simultaneous transport of REE, fluoride and carbonate is further underlined by an investigation of the solubility and speciation of REE in alkaline fluids using in situ X-ray absorption spectroscopy (Louvel et al , 2022). This provided evidence that alkaline fluids rich in F and CO 3 2– enhance hydrothermal mobilisation of LREE at temperatures ≥400°C and HREE at temperatures ≤ 200°C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experiments have provided evidence that alkali-rich fluids enable REEs, particularly HREEs, redistribution to form REE-rich minerals and enhance LREE and HREE mobilization at different temperatures with T ! 400 °C and 200 °C, respectively (Louvel et al, 2022). However, most of the HREE-rich granites in South China are peraluminous (Wu et al, 1992;Sanematsu and Watanabe, 2016).…”
Section: Petrogenesis Of the Granitoid Complexmentioning
confidence: 99%
“…This accelerates the segregation of highly evolved melts and volatile saturation in the peraluminous parental bodies. The exsolved ligand-rich liquids may transport REEs, particularly HREEs, at relatively low-temperature conditions (Louvel et al, 2022), and interact with granites during their emplacement (Fig. 10).…”
Section: Hree Enrichment In Peraluminous Granitementioning
confidence: 99%